Human Resource Placement System for Medical Record Work Unit at Private Hospitals in Medan City in 2024 - Nurhaliza, Nurhaliza; Simanjuntak, Esraida; Lubis, Siti Permata Sari; Sitorus, Mei Sryendang (Procedia of Engineering and Life Science, 2024)
The processing of a quality Medical Record unit requires a very important resource, namely human resources. The first step in producing skilled and reliable human resources requires planning in placing employees/employees who are suitable for their jobs. The process of placing human resources for medical record work units at Imelda Workers' General Hospital Indonesia, Adventist Hospital Medan and Eshmun General Hospital still found that some medical record employees were not in accordance with their qualifications because the employees had a diploma in computers, high school and a bachelor's degree in mechanical engineering. This can certainly lead to a lack of security in maintaining the confidentiality of medical record files, allowing duplication of medical record numbers, lack of quality of data produced and lack of quality of hospital services. The type of research used is descriptive research with a qualitative approach. The subjects of this study are 6 people, namely 1 HRD and 1 head of medical records at each of the Imelda Workers' General Hospital of Indonesia, Adventist Hospital Medan and Eshmun General Hospital. This sampling technique is by purposive sampling method. The results of the research that have been obtained are still medical record work unit officers who are not in accordance with their educational qualifications in the three hospitals, such as the registration section is not included in the medical record unit so that the officers who work are not medical recorder graduates. Work experience and physical health are factors that need to be considered in the placement of human resources and the average placement age of each officer is 25 to 40 years old, this age factor is considered with the intention of avoiding low productivity produced by the employee concerned. To the three hospitals, it is recommended that the placement of human resources in the medical record work unit is adjusted to their educational qualifications, experience, physical health and age.